Acute pancreatitis: update on management. Issue 8 (4th May 2015) - Nesvaderani, Maryam; Eslick, Guy D; Cox, Michael R
Summary: Acute pancreatitis is a common acute surgical condition associated with high morbidity and mortality in severe cases. New guidelines for management have recently been published by the American College of Gastroenterology and by the International Association of Pancreatology in collaboration with the American Pancreatic Association. The main differences between the new and previous versions of the guidelines relate to the use of endoscopic retrograde cholangiopancreatography (ERCP) and the addition of the new severity category of 'moderately severe acute pancreatitis' All patients with pancreatitis should have its cause determined by features of the history, results of laboratory tests (liver function tests, serum calcium triglyceride levels) and findings on transabdominal ultrasound. Those with idiopathic pancreatitis should have endoscopic ultrasound as a first‐line investigation. Acute pancreatitis should be managed with aggressive hydration with intravenous fluids and fasting. Oral feeding can be recommenced in mild pancreatitis once pain and nausea and vomiting have resolved. Patients with mild biliary pancreatitis should have a laparoscopic cholecystectomy during their index admission. In addition to aggressive intravenous fluid resuscitation and fasting, patients with severe pancreatitis should have enteral feeding (nasoenteric or nasogastric feeds) commenced 48 hours after presentation. Total parenteral nutrition should be avoided where possible. All patients with organ failure or severe pancreatitis as defined by the revised version of the Atlanta classification should be managed in an intensive care setting. Patients with biliary pancreatitis and concurrent cholangitis should have endoscopic retrograde cholangiopancreatography within 24 hours of presentation.